THE APPLICATION OF AUTOMATICALLY CONTROLLED EXPERIMENT FOR INTERDISCIPLINARY STUDENT MOTIVATION - Macerauskas, Eugenijus; Lucun, Andzej; Kozic, Antoni; Urbonas, Simonas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article analyses the application of automatically controlled physics laboratory experiment using information technology to enhance students’ motivation and interdisciplinary communication. The paper reveals how the application of interdisciplinary methods promotes students’ interest in studies, enhances the learning process and the quality of the students’ learning results from the very beginning of learning process. It was practically justified that during the fundamental science laboratory experiments, the first-year students realistically assess their future career prospects. Students become aware of the perspective of the further studies because they work with equipment designed by higher courses students. As a practical illustration of the authors and students of physics experiment designed automated equipment. The experiment system realized combines mechatronics, electronics, and programming technical areas corresponding to students' professional specialization. The system of physics laboratory experiment, has attracted particular interest students and the author conviction increased student motivation to learn.